Renal Injury, Abnormal Vitamin D Metabolism and Bone Homeostasis in Aged Rats With Insulin Resistance or Type 2 Diabetes Mellitus. (1st August 2008) - Chang-Quan, Huang; Bi-Rong, Dong; Qian, Xiao; Ping, He; Qun-Fang, Ding; Zhen-Chan, Lu; Xiao-Dong, Peng
Abstract : Objective: The study aimed to explore the relationship among renal injury, abnormal vitamin D metabolism, and bone homeostasis in insulin resistance (IR) or type 2 diabetes mellitus (T2DM). Design and Methods: The animal models of IR, T2DM, and T2DM treated with 1-alpha hydroxyvitamin D (1-α(OH)D) were established on 18-month-old male Wistar rats. Glucose infusion rates (GIR) and levels of urinary albumin (UA), serum 25-hydroxyvitamin D (25-(OH)D), serum 1, 25-dihydroxyvitamin D (1, 25-(OH)2 D), and bone mineral density (BMD) in lumbar vertebrae and femoral bone were measured. Results: Urinary albumin level in the rats with T2DM significantly increased, and there existed a significant and negative correlation between GIR and UA level in the rats with T2DM or IR. The levels of serum 25-(OH)D in all models were similar. The levels of serum 1, 25-(OH)2 D and BMD in the rats with IR were significantly higher than those in the rats with T2DM and were lower than those in normal control rats. In the aged rats with T2DM, administration of 1-α(OH)D had no effect on serum 25-(OH)D level although significantly increased the levels of serum 1, 25-(OH)2 D and BMD. There existed a negative correlation between the levels of serum 1, 25-(OH)2 D and UA in the rats with T2DM or IR. Conclusions: In IR or T2DM, abnormal vitamin D metabolism is characterized by 1, 25-(OH)2 D deficiency and is related to renal injury, and there also existed bone loss. In T2DM, both 1, 25-(OH)2 D deficiency and bone loss can be reversed by 1-α(OH)D.